Stereochemical assignment of varicosenone, a merosteroid flexible side chain, from the Indonesian sea slug Phyllidia varicosa using NMR and DFT-based NMR calculations - Novriyandi Hanif, Berlian Safriana Nuraulia, William Sean Ohlinger, Trianda Ayuning Tyas, Henny Dwi Yanti, Fabians Faisal Dinelsa, Dudi Tohir, Andi Setiawan, Anggia Murni, Junichi Tanaka (Journal of Applied Pharmaceutical Science, 2024)
A merosteroid with a flexible side chain named varicosenone (1a) was isolated from the sea slug Phyllidia varicosa collected from Banten, Jakarta, and South Sulawesi, Indonesia. The structure of 1a was elucidated using 1D and 2D nuclear magnetic resonance (NMR), mass spectrometry (MS) as well as density functional theory (DFT)--based NMR calculations. The relative configuration for the rigid portion (cyclic portion) was evidenced by nuclear Overhauser effect spectroscopy (NOESY) correlation, while the two-chiral centres on the flexible side chain were assessed by statistical comparison (including mean and max absolute, RMS error, and DP4 score) of experimental 13C chemical shifts with the results of the Boltzmann-weighted 13C chemical shifts calculated for each of the four potential stereoisomers. The result suggested a preference for two of the four possible stereoisomers (18R*, 21S*) and (18S*, 21S*). A similar analysis, accounting for the full set of 13C chemical shifts for the system, and only 1H shifts for the flexible side chain of DP4 for 13C and 1H chemical shifts of the portion favour (18R*, 21S*) stereoisomer. Therefore, 1a may have a relative configuration as 8S*, 9S*, 10R*, 13R*, 14S*, 17R*, 18R*, 21S*.
Keywords: DFT calculation, flexible molecule, NMR, nudibranch, merosteroid